ADA Diabetes Risk Test Adaptation in Indonesian Adult Populations: Can It Replace Random Blood Glucose Screening Test? - Dante S. Harbuwono; Muhammad Ikhsan Mokoagow; Nadya Magfira; Helda Helda (SAGE Publishing, 2021)
Aims The use of non-invasive and easily available assessment tools such as the ADA diabetes risk test is recommended for diabetes screening among general population. This study aims to assess the validity of the ADA diabetes risk test in screening for screening hyperglycemia in Indonesian population. Methods This cross-sectional study conducted at primary health care in Cibeber sub district at Cilegon city, Banten province, Indonesia. Subjects were aged ≥45 years old without a prior diagnosis of diabetes were recruited consecutively. The risk of hyperglycemia was measured using the ADA Diabetes Risk Test. Random capillary blood glucose (RcBG) with a cut-off value >140 mg/dL used as a comparison. Results From a total of 134 subjects, 23.13% of subjects (n = 31) had hyperglycemia. The ADA Diabetes Risk Test gave an area under the ROC curve (AUC) of 0.71 (95% CI: 0.60-0.81) with an optimal cut-off of value ≥5. The sensitivity of the ADA diabetes risk test in diagnosing hyperglycemia was 68% with a false-negative rate (FNR) of 32.26%. Meanwhile, at a cut-off value ≥4, the sensitivity of the ADA Diabetes Risk Test was 93% with an FNR of 9.7%. Conclusion ADA diabetes risk test provides a valuable result as a diabetes screening tool in the Indonesian population, thus promotes intervention strategies for population known to be at risk